Optimal location and sizing of distributed generation using particle swarm optimization with mutation strategy - Wong, Lye Yee (School of Electrical Systems Engineering, 2011)
The main objective of this research work is to develop a modified particle swarm optimization method in determining the optimal location and size of DG to be installed in the distribution system.